Salvage of side branch by provisional "TAP technique" using absorb™ bioresorbable vascular scaffolds for bifurcation lesions: First case reports with technical considerations. Issue 1 (27th February 2014) - Seth, Ashok; Sengottuvelu, G.; Ravisekar, V.
Abstract : Recent technological developments have led to the development of Absorb™ bioresorbable vascular scaffold (BVS) [Abbott Vascular, Santa Clara, USA] for percutaneous treatment of coronary artery disease by percutaneous coronary intervention (PCI). The BVS is now approved for use in many countries but experience in bifurcation lesions is limited and largely unreported and concerns still exist about its use across major side branches. We report for the first time, the successful use of the "T and Protrusion" (TAP) technique of deploying BVS into the side branch (SB) through the struts of main branch (MB) BVS to salvage a suboptimal result and threatened closure of a SB in three cases when treating bifurcation lesions with a planned single BVS strategy. The TAP technique was successful in all cases and there were no complications. All patients continue to do well at short‐term follow‐up. This case report provides information regarding the feasibility as well as technical and procedural insights when using BVS for bifurcation lesions. © 2014 Wiley Periodicals, Inc.